Gender differentiated discourse: a study of teacher discourse in the adult ESL classroom - Doray, Michele Brigitte Antoinette (Curtin University, 2005)
The purpose of this study was to investigate similarities and differences in the classroom discourse of male and female ESL teachers in the academic stream of one Western Australian tertiary institutions ELICOS program. Language and gender research generally suggests that males and females have different and quite distinctive communicative styles. This study attempts to examine if this finding is also manifested in male and female teachers discourse in adult ESL classrooms in the three main aspects of classroom interaction; giving explicit instructions, asking questions and providing verbal feedback, using Sinclair & Coulthards (1975) IRF framework. A sample of six teachers, three males and three females were observed through a process of non-participant observation and their lessons video-recorded in the naturalistic situation of the classroom in order to make a comparative analysis of their discourse.Teacher discourse in the three aspects of classroom interaction, namely, instructions, questioning and feedback, was examined with the purpose of exploring gender differences and similarities so that the reasons and implications for the manifestation of such similarities and differences can be further investigated. Conclusions were then made about the influence of traditional masculine and feminine speech styles on the discourse choices of the teachers.The discourse analysis found that more similarities than differences existed in the teachers classroom discourse supporting the notion that the choice of discourse features is dependent firstly on the context and secondly on the role of the interactants vis-à-vis each other in the community of practice. Although some differences emerged, the teachers in this study generally adopted a facilitative, cooperative speech style in their classroom discourse.